Evaluating the Financial Performance of BMT Al Fithrah After Rebranding as BMT Kedinding: A Case Study on Savings and Funding in Surabaya - Toyyibi, Abdul Majid; Hidayat, Imam; Farhan, Shohibatul (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study analyzes the shift in profitability experienced by BMT Al Fithrah following its transformation into BMT Kedinding in Surabaya after implementing a new strategy in the management of savings and funding. The primary focus of this research is to understand how the institution’s approach to managing savings  and financing has influenced its profitability post-rebranding and strategic realignment. Additionally, this study explores the key factors affecting profitability, including fund management policies and customer relationship practices.The objective of this research is to gain a comprehensive understanding of how changes in saving and funding strategies have impacted the profitability performance of BMT Kedinding. It also seeks to uncover managerial and operational insights that can support the institution’s future growth and financial sustainability. A qualitative case study approach was adopted, with data collected through in-depth interviews with BMT Kedinding’s management and direct observation of operational activities. The data were analyzed thematically to identify recurring patterns associated with improvements in profitability.The findings reveal that the transformation into BMT Kedinding, accompanied by more structured and focused management of savings and funding, has led to significant positive changes in the institution's profitability. This is evidenced by increased profits and the expansion of branches beyond Surabaya. Improved service quality, stronger customer relationships, and more efficient fund management have emerged as critical drivers of revenue growth and financial stability. Consequently, this study concludes that the post-rebranding saving and funding strategies have made a substantial contribution to enhancing the profitability of BMT Kedinding.